Studies of Chinese bayberry fruits on some physiological characters during the storage - HU Xi-qin; YU Xin; CHEN Li-geng (浙江大学学报. 农业与生命科学版, 2001)
Fruit of Chinese bayberry (Myrica rubra (Lour.) Sieb et Zucc) ‘Biqi’ culture were used in this study. The fruits were stored at the temperature of (21±1)℃, (11±1)℃ or (1±1)℃. By investigating the respiratory rate, ethylene production, POD, PG, soluble pectin and cellulose during the storage, the conclusion was as following: During the storage at (21±1)℃, the fruit soon showed some physiological characters of respiratory climacteric, such as reach the top of respiration and ethylene. The POD and PG activity is close relative with the senescence of Chinese bayberry fruits, but the cellulase may be not the major factor that result in the senescence of Chinese bayberry fruits.